Multi‐omics analysis reveals multiple mechanisms causing Prader–Willi like syndrome in a family with a X;15 translocation. Issue 11 (23rd July 2022) - Eisfeldt, Jesper; Rezayee, Fatemah; Pettersson, Maria; Lagerstedt, Kristina; Malmgren, Helena; Falk, Anna; Grigelioniene, Giedre; Lindstrand, Anna
Abstract: Prader–Willi syndrome (PWS; MIM# 176270) is a neurodevelopmental disorder caused by the loss of expression of paternally imprinted genes within the PWS region located on 15q11.2. It is usually caused by either maternal uniparental disomy of chromosome 15 (UPD15) or 15q11.2 recurrent deletion(s). Here, we report a healthy carrier of a balanced X;15 translocation and her two daughters, both with the karyotype 45, X, der(X)t(X;15)(p22;q11.2), −15. Both daughters display symptoms consistent with haploinsufficiency of the SHOX gene and PWS. We explored the architecture of the derivative chromosomes and investigated effects on gene expression in patient‐derived neural cells. First, a multiplex ligation‐dependent probe amplification methylation assay was used to determine the methylation status of the PWS‐region revealing maternal UPD15 in daughter 2, explaining her clinical symptoms. Next, short read whole genome sequencing and 10X genomics linked read sequencing was used to pinpoint the exact breakpoints of the translocation. Finally, we performed transcriptome sequencing on neuroepithelial stem cells from the mother and from daughter 1 and observed biallelic expression of genes in the PWS region (including SNRPN ) in daughter 1. In summary, our multi‐omics analysis highlights two different PWS mechanisms in one family and provide an example of how structural variation can affect imprinting through long‐range interactions.